Occupational challenges: burnout syndrome and brazilian legislation - Ribeiro, Marcos Andre; Franco de Oliveira, Rodrigo; P. Mundim Neto, Joaquim; R. Afonso, João Pedro; A. Souza, Shayra Kellen; de O. Moura, Barbara; C. Oliveira, Miriã; F. de Oliveira, Luís Vicente; R. Freitas Júnior, Wilson; N. R. Alves, Fernanda; B. S. Ribeiro Júnior, Jairo; Regina A. Galdeano, Patrícia; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
The article addresses the intersection between Burnout Syndrome and changes in Brazilian legislation, offering a holistic view of the clinical, psychological and legal implications of this phenomenon in the workplace. By exploring the trajectory of Burnout Syndrome as a new occupational condition, the analysis highlights the evolution of legal perspectives in Brazil. Using a desk research approach, the study reviews Brazilian legislation and analyzes related studies, revealing increasing attention to mental health and specific changes in legislation to protect workers. Furthermore, the ethical discussion and employers' responsibilities are addressed, expanding the scope of the analysis. The research contributes to an ongoing dialogue about mental health, legislation and work practices, promoting a deeper understanding and prevention of Burnout in Brazilian professional environments.